2019
DOI: 10.1002/cti2.1073
|View full text |Cite
|
Sign up to set email alerts
|

Furin‐mediated protein processing in infectious diseases and cancer

Abstract: Proteolytic cleavage regulates numerous processes in health and disease. One key player is the ubiquitously expressed serine protease furin, which cleaves a plethora of proteins at polybasic recognition motifs. Mammalian substrates of furin include cytokines, hormones, growth factors and receptors. Thus, it is not surprising that aberrant furin activity is associated with a variety of disorders including cancer. Furthermore, the enzymatic activity of furin is exploited by numerous viral and bacterial pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
319
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(329 citation statements)
references
References 148 publications
2
319
0
8
Order By: Relevance
“…Strikingly, the 2019-nCoV S-protein sequence contains 12 additional nucleotides upstream of the single Arg↓ cleavage site 1 (Figs. 1B and 2) leading to a predictively solventexposed PRRAR↓SV sequence, which corresponds to a canonical furinlike cleavage site (Braun and Sauter, 2019;Izaguirre, 2019;Seidah and Prat, 2012). This furin-like cleavage site, is supposed to be cleaved during virus egress (Mille and Whittaker, 2014) for S-protein "priming" and may provide a gain-of-function to the 2019-nCoV for efficient spreading in the human population compared to other lineage b betacoronaviruses.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…Strikingly, the 2019-nCoV S-protein sequence contains 12 additional nucleotides upstream of the single Arg↓ cleavage site 1 (Figs. 1B and 2) leading to a predictively solventexposed PRRAR↓SV sequence, which corresponds to a canonical furinlike cleavage site (Braun and Sauter, 2019;Izaguirre, 2019;Seidah and Prat, 2012). This furin-like cleavage site, is supposed to be cleaved during virus egress (Mille and Whittaker, 2014) for S-protein "priming" and may provide a gain-of-function to the 2019-nCoV for efficient spreading in the human population compared to other lineage b betacoronaviruses.…”
Section: Tablementioning
confidence: 99%
“…Indeed, it was recently shown that in an effort to limit viral infections, host cells that are infected by a number of viruses provoke an interferon response to inhibit the enzymatic activity of furin-like enzymes. It was also demonstrated that HIV infection induces the expression of either the protease activated receptor 1 (PAR1) (Kim et al, 2015) or guanylate binding proteins 2 and 5 (GBP2,5) (Braun and Sauter, 2019) that restrict the trafficking of furin to the trans Golgi network (PAR1) or to early Golgi compartments (GBP2,5) where the proprotein convertase remains inactive. Altogether, these observations suggest that inhibitors of furin-like enzymes may contribute to inhibiting virus propagation.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Genomic analysis of the new CoV has shown that its SP differs from that of other viruses (Du et al, 2017;Li, 2016), indicating that the protein has a site activated by a HC enzyme called furin (Millet & Whittaker, 2015) (Figure 1). This enzyme normally cleaves and activates a wide range of substrates in different organisms (Figure 2a) (Braun & Sauter, 2019). This enzyme is found in many human tissues, including the lungs, liver and small intestine, which means that the virus has the potential to invade different organs (Belouzard et al, 2012;Heald-Sargent & Gallagher, 2012;Scamuffa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Here, Braun and Sauter review the roles of furin in these processes, as well as the history and future of furin-targeting therapeutics. 7 They also discuss their recent work revealing how two IFN-cinducible factors exhibit broad-spectrum inhibition of IAV, measles (MV), zika (ZikV) and HIV by suppressing furin activity. 8 Over the coming decade, I expect to see an ever-finer spatiotemporal resolution of host-oriented therapies to achieve safe, effective and broad-spectrum yet costeffective therapies for clinical use.…”
mentioning
confidence: 99%